Phototherapy in the treatment of atopic dermatitis. Is monotherapy possible? - Yu. A. Gallyamova; A. R. Khasanova (Лечащий Врач, 2024)
Background. Currently, in the treatment of atopic dermatitis universally recognized phototherapy narrowband ultraviolet B (narrow-wave UVB therapy) with a maximum emission at a wavelength of 311 nm, the effectiveness of which has been confirmed by numerous studies. Phototherapy occupies the second line of therapy after unsuccessful treatment with emollients and topical glucocorticosteroids, it can be used both in mono and combined therapy. In addition, there is steroidophobia among patients, often the dermatologist is approached by patients who refuse not only systemic therapy, but also topical application of glucocorticosteroids, but readily agree to physical therapy, paying attention to the overall safety of phototherapy UVB-311 nm.Results. The article presents the results of clinical studies of the effectiveness of narrow-band phototherapy UVB-311 nm in patients with atopic dermatitis in the form of monotherapy in combination with emollients. UVB-311 nm phototherapy is an effective method for treatment many skin diseases, however, there are still no clear recommendations on the use of the method depending on the severity and duration of the process. The authors, based on their own observations, concluded that monotherapy with narrow-band phototherapy UVB-311 nm is highly effective in patients with atopic dermatitis with a SCORAD index of no more than 40 points; in more severe cases, it is impossible to achieve a positive therapeutic effect with monotherapy. The authors demonstrated clinical cases from their own practice of using narrow-band phototherapy UVB-311 in patients with atopic dermatitis as monotherapy.